The Impact of In-house Attending Surgeon Supervision on the Rates of Preventable and Potentially Preventable Complications and Death at the Start of the New Academic Year. Issue 11 (November 2013) - Inaba, Kenji; Hauch, Adam; Branco, Bernardino C.; Cohn, Stephen; Teixeira, Pedro G. R.; Recinos, Gustavo; Barmparas, Galinos; Demetriades, Demetrios
The purpose of this study was to examine the impact of in-house attending surgeon supervision on the rate of preventable deaths (PD) and complications (PC) at the beginning of the academic year. All trauma patients admitted to the Los Angeles County 1 University of Southern California Medical Center over an 8-year period ending in December 2009 were reviewed. Morbidity and mortality reports were used to extract all PD/PC. Patients admitted in the first 2 months (July/ August) of the academic year were compared with those admitted at the end of the year (May/June) for two distinct time periods: 2002 to 2006 (before in-house attending surgeon supervision) and 2007 to 2009 (after 24-hour/day in-house attending surgeon supervision). During 2002 to 2006, patients admitted at the beginning of the year had significantly higher rates of PC (1.1% for July/ August vs 0.6% for May/June; adjusted odds ratio [OR], 1.9; 95% confidence interval [CI], 1.1 to 3.2; P < 0.001). There was no significant difference in mortality (6.5% for July/August vs 4.6% for May/ June; adjusted OR, 1.1; 95% CI, 0.8 to 1.5; P = 0.179). During 2007 to 2009, after institution of 24-hour/day in-house attending surgeon supervision of fellows and housestaff, there was no significant difference in the rates of PC (0.7% for July/August vs 0.6% for May/June; OR, 1.1; 95% CI, 0.8 to 1.3; P = 0.870) or PD (4.6% for July/August vs 3.7% for May/June; OR, 1.3; 95% CI, 0.9 to 1.7; P = 0.250) seen at the beginning of the academic year. At an academic Level I trauma center, the institution of 24-hour/day in-house attending surgeon supervision significantly reduced the spike of preventable complications previously seen at the beginning of the academic year.